Actual Problems of National Historiography of Cultural and Enlightening Activity of Jesuits in Belarus - T. I. Nareiko (Наука и техника)
Cultural and enlightening activity of Jesuits in Belarus has been studied as a rule by Belarussian scientists from the point of view of forced catholic spreading ideology. Jesuit order was considered as an instrument of aggravation of inter-confessional relations in Belarus. It is regretful that it happened because this problem was not selected for special cultural investigation by national historians. Hence it appears that a proper place of Jesuit activity in the history of culture and spiritual life in Belarus is not determined yet.